2020
DOI: 10.1016/j.foodchem.2020.126838
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitro biological activities of cardoon (Cynara cardunculus L. var. altilis DC.) seeds as influenced by viability

Abstract: Chemical composition and in vitro biological activities of cardoon (Cynara cardunculus L. var. altilis DC.) seeds as influenced by viability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
(46 reference statements)
3
22
0
Order By: Relevance
“…Moreover, it is very common in natural matrices to exhibit variable effectiveness in various antioxidant activity assays, since different compounds and mechanisms are involved in different assays [41,42]. Similarly to our study, the reduced variety of tocopherols found in cardoon bracts has also been reported for other plant parts such as heads and seeds, indicating that α-tocopherol is the main vitamin E isoform detected in the species [30,40,43].…”
Section: Tocopherols Organic Acids and Free Sugars Contentsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, it is very common in natural matrices to exhibit variable effectiveness in various antioxidant activity assays, since different compounds and mechanisms are involved in different assays [41,42]. Similarly to our study, the reduced variety of tocopherols found in cardoon bracts has also been reported for other plant parts such as heads and seeds, indicating that α-tocopherol is the main vitamin E isoform detected in the species [30,40,43].…”
Section: Tocopherols Organic Acids and Free Sugars Contentsupporting
confidence: 85%
“…On the contrary, the lowest content of tocopherols was detected in sample C5 (11.7 µg/100 g dw). Due to the fact that tocopherols are antioxidant molecules, they are susceptible to oxidation reactions; thus, they can be strongly influenced by the various environmental conditions to which the plant is subjected throughout its growth cycle [30]. This fact could justify the variations in the content of tocopherols in bracts, as well as the fact that in our previous study [39], phenolic compounds content showed a decrease with increasing maturity, explained by the lignification of bracts tissues [12].…”
Section: Tocopherols Organic Acids and Free Sugars Contentmentioning
confidence: 75%
“…The α-tocopherol was the only isoform identified and was detected in all the studied samples. Tocopherols are antioxidant compounds with high capacity to undergo oxidation reactions, therefore fluctuations of environmental conditions that may induce plant stress throughout the growth cycle of the heads could be a justification for the observed fluctuations in tocopherols content [23]. As shown in Figure 2, variable climatic conditions prevailed during and prior the harvesting period in our study, especially a dry period during March-May which could be associated with stressful conditions that resulted in an increase of tocopherols content.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, considering the concomitant decrease in total sugars content at late maturity stages, the increase of organic acids especially in sample Car E could be explained by the increased requirements in osmolytes as a mechanism of cardoon plants to overcome stress conditions induced by the high mean and max temperatures and the concomitant low precipitation (see Figure 2) [52,53]. Compared to other reports, cardoon heads revealed greater variety and lower abundance of organic acids than seeds [23,47], while organic acids profile was similar to aerial parts [54]. Finally, the high quinic acid in sample Car E could be valorized for its confirmed high antioxidant potential [55,56].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation